Mediating role of job satisfaction on internal corporate social responsibility practices and employee engagement in higher education sector - Hossen, Md. Monir; Chan, Tak Jie; Mohd Hasan, Nurul Ain (Academy of Taiwan Information Systems Research, 2020)
The study aims to investigate the relationship between internal corporate social responsibility (ICSR) practices and employee engagement through job satisfaction as a mediating variable. The ICSR dimensions are comprised of employee empowerment, education and training, employment stability, as well as a working environment. This study is based on the social exchange theory to explore the relationship between the above factors and ICSR. In this study, purposive sampling was adopted. A quantitative (survey) method was employed, generating 93 valid responses. The data was then analyzed using Partial Least Square Structural Equation Modelling through Smart-PLS 3.0. The results revealed that ICSR practices, namely employee empowerment, and employment stability contributed positively to job satisfaction. However, training & education and working environment were found not significant to job satisfaction. In addition, job satisfaction has a positive influence on employee engagement. The results of the study found that except for training, education, and the work environment, job satisfaction mediates the relationship between ICSR practices and employee engagement. Conclusion, implications of the findings, and suggestions for future study are also discussed.